THE EFFECT OF ZOOM MEETING ON E-LEARNING IN STUDENT SPEAKING SKILL - Fitriani Guci; Leroy Holman Siahaan (Department of English Education, Universitas Panca Sakti Bekasi, 2021)
This research aims to find out the effect of zoom meeting on e-learning in student speaking skill at ninth grade of SMPN 35 Bekasi. The use of zoom meetings supports the learning process in the covid-19 pandemic. This research was conducted in July 2021. The analysis used in quantitative research is experimental design. This research sample is 40 students in grade ninth with divided into two groups, namely a control group with a total of 20 students and an experiment group with a total of 20 students. Data collection is carried out with a test technique system to get the results of students' speaking skills. Statistical test using SPSS 22. The results showed that there was a difference between the control group and the experiment group. This can be proven by; 1. Instrument test results with a reliability level of 0.800 which means that the results are valid. 2. 2. the test result t is a significance score (2-tailed) from the test result of 0.00 < 0.05 so that a sig score of 0.00 is seen to show the effect of using zoom meetings in speech ability in SMPN 35 Bekasi.